Estudo comparativo da ação de bradicinina e cxcl12 na neurogênese no camundongo adulto - Pioli, Natalia Muehringer Alves [UNIFESP] (2016)
The discovery of neurogenesis in specific regions of the adult encephalon has arised new perspectives for cell therapy and regeneration of the nervous tissue. The mechanisms involved in maintaining neural stem cells in those specific regions of the adult brain are not completely understood yet, although the potential of neural stem cells to generate neurons and glia in pathological situations have been already recognized. Studies performed in the last years have demonstrated the role of bradykinin (BK) in the induction, progression and phenotypic determination of neural stem cell, as well as in migration. Despite that, the intracellular signaling pathways that are activated by BK, resulting in modulation of adult neural stem cell responses are not completely known. BK is one of the inflammatory mediators secreted in response a central nervous system injury, together with other anti- and proinflammatory cytokines. Among the cytokines secreted after an injury is the chemokine CXCL 12, which stimulates neural stem cell migration from the subventricular zone to the injury site. It has already been described that BK and " CXCL 12 are associated to the pathophysiology of neuropathic pain. Based on that, we propose to evaluate similarities between BK and CXCL 12 in the induction of proliferation, migration and differentiation of adult neural stem cells in vitro.